2014
DOI: 10.1111/ajco.12191
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sorafenib in combination with gemcitabine in patients with advanced hepatocellular carcinoma: A multicenter, open‐label, single‐arm phase II study

Abstract: The combination of sorafenib and gemcitabine in advanced hepatocellular carcinoma is generally well tolerated and has modest clinical efficacy. The median OS is up to 1 year. However, well-designed randomized controlled trials with a sorafenib alone comparator arm are needed to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In another study, Liu et al reported that GEMOX combined with sorafenib as first-line therapy followed by sorafenib as maintenance therapy was effective with manageable toxicity for treatment of advanced HCC [150]. Furthermore, the combination of sorafenib and gemcitabine showed modest clinical efficacy with good toleration in advanced HCC [152]. In addition, compared with doxorubicin monotherapy, sorafenib plus doxorubicin resulted in greater median time to progression, overall survival, and progressionfree survival [153].…”
Section: Combination Of Cytotoxic Chemotherapeutic Agentsmentioning
confidence: 99%
“…In another study, Liu et al reported that GEMOX combined with sorafenib as first-line therapy followed by sorafenib as maintenance therapy was effective with manageable toxicity for treatment of advanced HCC [150]. Furthermore, the combination of sorafenib and gemcitabine showed modest clinical efficacy with good toleration in advanced HCC [152]. In addition, compared with doxorubicin monotherapy, sorafenib plus doxorubicin resulted in greater median time to progression, overall survival, and progressionfree survival [153].…”
Section: Combination Of Cytotoxic Chemotherapeutic Agentsmentioning
confidence: 99%
“…Our previous results [13] revealed that the combination of Sorafenib and chemotherapy may not improve the clinical outcome. A randomized phase II trial comparing Sorafenib alone with Sorafenib plus GEMOX demonstrated that the main objective (4-month PFS rate >50%) was achieved but was comparable in both arms (54% and 64% respectively), and median PFS and OS were not significantly different in the two arms.…”
Section: Discussionmentioning
confidence: 94%
“…Sorafenib has been combined with anti-angiogenic agents, MEK/ERK pathway inhibitors, mTOR pathway inhibitors, histone deacetylase inhibitors, EGF/EGFR pathway inhibitors, and HGF/c-Met pathway inhibitors. 31 Other agents such as interferon, 32 selumetinib, 33 capecitabine, 34 tegafur-uracil, 35 gemcitabine and oxaliplatin (GEMOX), 36 , 37 and gemcitabine alone 38 have also been evaluated but to date no treatments involving combinations containing sorafenib have succeeded in phase III trials.…”
Section: Approved First-line Agents For Hccmentioning
confidence: 99%